Environment-assisted cracking of cast WE43-T6 magnesium - Marrow, T; Bin Ahmad, A; Khan, I; Sim, SMA; Torkamani, S (2004)
Environment-assisted cracking of WE43 cast magnesium (4.2 wt.% Yt, 2.3 wt.% Nd, 0.7% Zr, 0.8% HRE) in the T6 peak-aged condition was induced in ambient air in notched specimens. The mechanism of fracture was studied using electron backscatter diffraction, serial sectioning and in situ observations of crack propagation. Cracks initiated at the intergranular brittle intermetallic, and propagated by transgranular cleavage. These observations imply that a microstructural model for the static fatigue limit in cast magnesium alloys may be developed which includes the effects of notch-like defects such as porosity. © 2004 Elsevier B.V. All rights reserved.